A High Efficient Electrocatalytic Activity of Metal‐organic Frameworks ZnO/Ag/ZIF‐8 Nanocomposite for Electrochemical Detection of Toxic Heavy Metal Ions. Issue 3 (31st August 2022) - Arabbani, Finly K.; Vasu, Dhanapal; Sakthinathan, Subramanian; Chiu, Te‐Wei; Liu, Ming‐Che
Abstract: A novel electrochemical sensor on ZIF‐8 nanocomposites (Ag/ZnO/ZIF‐8) was developed to analyze the mercury ions (Hg 2+ ). The ZIF‐8 materials are one of the 3‐dimensional porous metal‐organic frameworks with highly accessible pores and great surface area. The ZIF‐8 nanocomposites were prepared through simple sol‐gel methods and their physio‐chemical properties were characterized via different analytical analyses. As a result of cyclic voltammetry, Ag/ZnO/ZIF‐8 exhibited a better electrocatalytic behavior towards the detection of mercury ions (Hg 2+ ). Furthermore, the composite modified electrode was then inspected as a sensor for DPV detection of mercury ions. The nanocomposite sensor performed a wide linear range from 0.5 μM to 140 μM with a low detection limit of 40 nM, and high sensitivity of 56.06 μA μM −1  cm −2 . Moreover, the ZIF‐8 composite sensor showed a higher selectivity toward the detection of mercury ions (Hg 2+ ). The real‐time applications of the ZIF‐8 composites sensor were inspected in various samples with good sensitivity. Abstract :